1996
DOI: 10.1088/0957-0233/7/3/027
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of multiphase flow in packed beds by computer-assisted x-ray tomography

Abstract: The high resolution which can be obtained by computer-assisted x-ray tomography is used to investigate various scale heterogeneities of the flow texture characterizing multiphase flow in packed beds. The direct counting of 'irrigated' pixels allows the determination of the number of individual liquid rivulets as well as their size. The evolution of the liquid flow texture versus the liquid velocity agrees quite well with the predictions of a percolation-based model. This agreement is further confirmed by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 19 publications
0
26
0
3
Order By: Relevance
“…Each of the different possible tomographic techniques has its advantages and drawbacks: the X-ray tomography used by Toye et al (1996Toye et al ( , 1997 is well suited for very small velocities, since the gasliquid repartition has to be constant during a measurement, which is quite slow. In the present work, the capacitive tomography developed by the team of Hanover was used (Reinecke, 1996;Mewes, 1996a, 1996b;Reinecke et al, 1998) found in the mentioned papers.…”
Section: Capacitive Tomographymentioning
confidence: 99%
“…Each of the different possible tomographic techniques has its advantages and drawbacks: the X-ray tomography used by Toye et al (1996Toye et al ( , 1997 is well suited for very small velocities, since the gasliquid repartition has to be constant during a measurement, which is quite slow. In the present work, the capacitive tomography developed by the team of Hanover was used (Reinecke, 1996;Mewes, 1996a, 1996b;Reinecke et al, 1998) found in the mentioned papers.…”
Section: Capacitive Tomographymentioning
confidence: 99%
“…An X-ray CT system was developed by Toye et al [24] specifically for X-ray CT flow visualization of liquid holdup and maldistribution in packed beds. The X-ray system produced a fan beam that was captured with a linear array of 1024 photodiodes, each 1.66 mm wide.…”
Section: Examples Of X-ray Ct Imaging Of Fluid Flowsmentioning
confidence: 99%
“…This makes the reconstruction easier, but, because of the detection systems and source strength, data acquisition is typically slow. Of the ionizing radiation (hard field) techniques, X-ray imaging is safest because the sources only emit X-rays when they are powered and their energy can be controlled by varying the input voltage [18,24]. Toye et al [24] also note that X-rays are preferred over c-rays because the X-rays provide better spatial resolution due to improvements in X-ray detector technology in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive review discussing applications of GDT to multiphase flows is provided by Munshi (1990). Typical applications have included two-phase gas-liquid pipe flows for the nuclear industry (Hewitt, 1978), saturation measurements in porous media (Reda et al, 1981;Brown et al, 19931, gas-solid fluidized beds (MacCuaig et al, 1985;Dyakowski, 1996), gas-liquid flow in packed beds (Toye et al, 1996), particle-laden liquid flows (Shollenberger et al, 1997b), horizontal stratified three-phase pipe flow (Pan and Hewitt, 19951, and bubble columns (Kumar et al, 1995;Shollenberger et al, 1995ab;Adkins et al, 1996;Shollenberger et al, 1997a;Torczynski et al, 1995;Torczynski et al, 1996ac).…”
mentioning
confidence: 99%